Association between body roundness index with femoral neck bone mineral density, osteoporosis, and FRAX score in middle-aged and older adults: A cross-sectional study - Wentao Xiao; Yi Wang; Taichuan Xu; Chao Li; Xian Zhang (Experimental Gerontology)
Background: The clinical usefulness of the body roundness index (BRI) in predicting bone health outcomes, including femoral neck bone mineral density (FN BMD), osteoporosis, and fracture risk assessment (FRAX) scores, remains unvalidated in middle-aged and elderly populations. Methods: Based on NHANES data from 2013 to 2014, we included 2215 adults. Weighted multiple linear regression and logistic regression models were used to investigate the relationship between BRI and FN BMD, osteoporosis, and FRAX scores. Non-linear correlations were examined using the restricted cubic spline (RCS) model. Results: The regression analyses indicated a robust positive correlation between BRI and FN BMD, with each unit boost in BRI leading to a 0.018 g/cm2 increase in FN BMD (β = 0.018, 95 %CI: 0.015, 0.021). A substantial negative association was found between BRI and osteoporosis (OR = 0.804, 95 %CI: 0.714, 0.906). Furthermore, the BRI was significantly and negatively associated with FRAX scores. RCS revealed a linear positive correlation between BRI and FN BMD and a negative linear correlation with osteoporosis and a negative non-linear correlation with FRAX scores. Conclusion: This cross-sectional study elucidated that the BRI demonstrates a complex relationship with various bone health parameters, including a significant positive correlation with FN BMD and a significant negative correlation with osteoporosis prevalence and FRAX scores. However, it was unable to establish a causal relationship between the BRI and these various bone health parameters.